Introduction to procurement in the public sector - Bauccio-Teschlog, Theresa R. M.; King, Ronald (Procurement officer); Tommie, William J., Jr (Cornerstones of public procurement, 2025)
Public procurement is an exciting, challenging profession that is responsible for the procurement of goods, services, and construction at every level of government, estimated at nearly 13 trillion US dollars worldwide. Public procurement professionals often work behind the scenes to promote responsive and responsible government, improving the quality of life for the people in their communities. Introduction to Procurement in the Public Sector, Fourth Edition is designed to provide an overview of the field, introduce the reader to the public procurement profession, and explore the wide variety of responsibilities and practices that must be addressed throughout the public procurement cycle.This book offers a thorough and complete overview of the function and profession of public procurement, explores legal frameworks, examines contract administration, and investigates a variety of solicitation methods and processes, with an emphasis on what happens post-award, including surplus and disposal. Introduction to Procurement in the Public Sector, Fourth Edition provides the reader with a comprehensive understanding of the public procurement profession, as well as insight into methods, strategies, and tools for successful and ethical procurement practice. The book is an ideal primer for those entering the field of public procurement and serves as a comprehensive textbook for courses in public administration, supply chain management, and related fields of study.